The Southeastern Librarian, Vol.40, No.02, Summer 1990 - Curry, Elizabeth; Hughes, Raylynn; Tucker, David (The Southeastern Library Association, 1990)
The Southeastern Librarian, Vol.40, No.02, Summer 1990. Periodical.
1 electronic record. 84 pages. Scanned from original document. Contents include: SELA Officers and Staff - cover verso, State Library Association Officers - cover recto, President's Page - 45, Editor's Musings - 46, Introduction to Special Issue by Clarence Walters - 47, Three Days in February: A Summary Report on the Role of Information in the Economy o f the Southeast Conference by Joel Sigmon - 48, Impressions o f the Conference on the Role of Information in the Economy of the Southeast by Ron Steensland - 52, Notes on Expanding the Ideas from the Conference on Information and the Economy of the Southeast by David L. Kallenborn - 54, Reflections from a Participant by Jeff S. Thompson - 55, Keynote Speech by David Osborn - 57, The Future of Economic Development in the Region by Jesse L. White, Jr. - 61, The Economy of the Rural Southeast by Rick Carlisle - 65, The Economy of the Urban South by Roy Bahl and David Sjoquist - 69, Visualization and Information: Computer Images by Earl R. MacCormac - 71, Information and the Development o f Rural North Carolina by Howard McGinn - 75, Meeting AT&T’s Needs for Information by W. David Penniman - 81, Overcoming Political and Financial Barriers by Barratt Wilkins - 85, Implementing Change in the Development of an Information Infrastructure by Ralph Russel - 87, Raising Anchor, Casting Off: Information Technology and Economics in the Southeast by Jerry Campbell - 93, Closing Remarks: An Overview of the Conference and a Look to the Future by Edward Holley - 95. SELA ASSOCIATION NEWS: Candidates - 118, Conference News - 114, Financial Report - 120, Guidelines for SELn Submissions - 44, Membership Form - 121, New Members - 111, State Editors - 119. DEPARTMENTS: Bulletin Board - 105, Calendar - 122, Keeping Up - 107, New & Useful - 106, People - 108, Stateside View - 101.
Keywords: Periodicals | Southeastern Library Association